Comparison of Adenosine Deaminase, Zinc, Magnesium, Lipid Profile, and some Micronutrient Elements and their Relation with CD4 Counts in Human Immunodeficiency Virus Positive and Negative Patients - Abdollahi, Alireza (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: There is strong evidence regarding the patterns of alteration in the blood parameters in human immunodeficiency virus (HIV)-positive patients. However, no consensus has been reached in this regard and the results vary from different regions and studies. Our study aims to report these patterns in a population of HIV-infected patients in Iran. MATERIALS AND METHODS: We studied two groups of HIV-infected and HIV-negative patients. One hundred and fourteen subjects were enrolled in each group; blood parameters were compared in these two. RESULTS: Variables of HIV-negative patients changed as follows compared to HIV-positive patients: with regard to the hematological variables, CD4+↓; CD8+↓; WBC↓; RBC↓; HCT↓; MCV↑; MCH↑; MCHC↑; PLT↓; EOS↑; and BASO↑; and among the metabloic parameters, TG↓; CH↑; HDL↓; LDL↓, MG↑; ZN↑; P↑; and ADA↓, which showed significnat differences between groups (P < 0.05). CONCLUSION: We conclude that HIV infection affects hematopoiesis by diminishing the hematological productivity parameters and increasing red blood cell related morphology, along with a different pattern of lipid profile (decreased TG, LDL, HDL, and increased CH) and serum micronutrients (elevated concentration of serum trace elements) in our population of study.